Development of real-time cost analysis application for irrigation construction projects using extreme programming methodology - Sihombing, Denny Jean Cross (SEAN Institute, 2024)
This research aims to address the challenges of cost management in irrigation construction projects by developing a real-time cost analysis application. Key issues involve information delay, complexity of cost factors, and limitations of traditional development models. The research method consists of three crucial stages: data collection, application development using the Extreme Programming method, and user acceptance analysis. Data was collected through interviews, field observations, and document analyses. The application was developed with features such as budget management, real-time cost monitoring, risk analysis, project team management, and project financial reports. The pilot test involved test scenarios involving active users. The results showed success in managing budgets, real-time cost monitoring, and risk analysis, with a high success rate. The contribution is developing a responsive and adaptive application that meets the needs of irrigation construction projects, overcomes the limitations of traditional development models, and improves the efficiency and responsiveness of project cost management.